ANALYSIS OF THE IMPLEMENTATION OF THE POLICY OF CHANGING THE MAP OF APPARATUS POSITIONS AT BRIDA MEDAN CITY - Farhan Abrar; Audia Junita; Maksum Syahri Lubis (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to analyze the implementation of the policy of changing the map of apparatus positions at the Regional Research and Innovation Agency (BRIDA) of Medan City, identify supporting and inhibiting factors, and provide recommendations for improvement. The research method used is qualitative descriptive with a case study approach. Primary data was obtained through in-depth interviews and observations, while secondary data was obtained from official documents and related regulations. The results of the study show that the implementation of the policy is carried out through position mapping, cross-agency coordination, socialization, and improving the competence of ASN. The change in the position map shifted the orientation from structural to functional in accordance with the national bureaucratic reform policy. Supporting factors include a clear legal basis, support from regional leaders, effective coordination, and the readiness of some ASN. The obstacles found include limited understanding of ASN, resistance to old work culture, limited competent human resources, and a performance appraisal system that is not optimal. The conclusion of this study shows that the implementation is quite effective, but it requires strengthening competency aspects, fostering a new work culture, adding qualified human resources, and improving the performance appraisal system.